Relationship between anthropometric parameters and sensory processing in typically developing brazilian children with a pediatric feeding disorder - Junqueira, Patrícia; Dos Santos, Dyandra Loureiro Caron; Lebl, Mariana Célia Guerra; de Cesar, Maria Fernanda Cestari; Dos Santos Amaral, Carolina Antunes; Alves, Thais Coelho [UNESP] (MDPI, 2021)
In this study, we aimed to relate anthropometric parameters and sensory processing in typically developing Brazilian children diagnosed with a pediatric feeding disorder (PFD). This was a retrospective study of typically developing children with a PFD. Anthropometric data were collected and indices of weight-for-age, length/height-for-age, and body mass index-for-age (BMI-for-age) were analyzed as z-scores. Sensory profile data were collected for auditory, visual, tactile, vestibular, and oral sensory processing. We included 79 medical records of children with a PFD. There were no statistically significant (p > 0.05) relationships between the anthropometric variables (weight-, length/height-, or BMI-for-age) and the sensory variables (auditory, visual, tactile, vestibular, or oral sensory processing). In conclusion, we found no relationship between anthropometric parameters and sensory processing in the sample of typically developing Brazilian children diagnosed with a PFD under study.
Keywords: Anthropometry; Feeding problems; Food refusal; Food selectivity; Modalities; Pediatric feeding and eating disorders; Pediatric feeding disorders; Sensorial; Sensory processing